FUTURE DRIVERS OF RURAL PROSPERITY IN KNOWLEDGE AGE: LITHUANIAN CASE - Vilke, Rita; Gedminaite-Raudone, Zivile; Cvijanovć, Drago (Economics of Agriculture, 2019)
The knowledge age greatly shaped societys understanding of what goes beyond the agribusiness and sharply raised the question of farmers responsibilities on the way they do farming in relation to the payments they receive as public support. Therefore the new rural prosperity drivers in knowledge age calls for the new principles of European Union support distribution for agriculture and rural development. The aim of this research is to explore future drivers of rural prosperity based on knowledge society measures. It is argued, that the upcoming European Union rural prosperity is guided by knowledge philosophy encompassing the nexus among innovating, networking and giving back to society. Original empirical data, collected in Lithuanian in 2017, explores farmers attitudes towards listed knowledge society measures in relation to farm size and other relevant characteristics. Research findings suggest more promising directions for agriculture and rural development that contributes better for rural prosperity in knowledge age.